Rizatriptan for acute migraine headaches in adults - Ling, Rebecca (Cochrane Database Syst Rev, 2010)
This is the protocol for a review and there is no abstract. The objectives are as follows: The objective of the review will be to determine the efficacy and tolerability of rizatriptan compared to placebo and other active interventions in the treatment of acute migraine headaches in adults.